Editorial: Portable antiquities: archaeology, collecting, metal detecting - Suzie Thomas (Internet Archaeology, 2013)
Metal detecting and archaeology do not always coexist peacefully. Indeed, even in the current climate of participation and inclusion within public and community archaeologies, there are still issues of trust to address, relating to both metal-detector users and archaeologists. While in the UK there have been disagreements between archaeologists and metal-detector users over the years, there have also been some significant steps made in encouraging metal-detector users to cooperate with the archaeological sector. Perhaps the most successful and best known of these is the Portable Antiquities Scheme (PAS), active across England and Wales. Add to this mix those that provide the commercial demand for metal-detected finds, the dealers and private collectors, and a clash of interests and motivations seems inevitable. Most would hope that relationships, positive in many cases but also problematic, will improve, both in the interests of enhancing the recording of non-stratified finds, and of promoting a publicly accessible and inclusive archaeology. However, is this an inevitable progression, or ultimately unachievable?